Analisis PT ESSA Industries Indonesia Tbk sebagai Saham Investasi di Bursa Efek Indonesia - Firda Ananda Yulia Sari; Yeny Novita Fitriani; Achmad Fariz Fizabillah; Alvazaki Ikbar Maulana; I. Made Suparta (LPPM Politeknik Pratama, 2025)
This study aims to analyze the feasibility of PT ESSA Industries Indonesia Tbk's stock as an investment instrument on the Indonesia Stock Exchange (IDX). The research method employed is a literature review, examining the company’s 2023 financial statements, stock trading dynamics, and the impact of macroeconomic factors such as exchange rates, inflation, and GDP growth. Additionally, the single index model is applied to assess ESSA’s position within an optimal investment portfolio. The findings reveal that ESSA demonstrates stable financial performance, a healthy capital structure, and promising growth prospects in the energy and chemical sectors. Nevertheless, stock price volatility due to global commodity price fluctuations and economic conditions remains a critical concern for investors. Considering its potential returns and manageable risk level, ESSA’s stock is considered a viable component in a diversified investment portfolio.